2017
DOI: 10.1080/1028415x.2017.1354511
|View full text |Cite
|
Sign up to set email alerts
|

High-fat simple carbohydrate (HFSC) diet impairs hypothalamic and corpus striatal serotonergic metabolic pathway in metabolic syndrome (MetS) induced C57BL/6J mice

Abstract: The central and peripheral serotonergic pathway is affected differentially by both the type of diet consumed and the duration for which the diet is consumed. The hypothalamic, striatal and plasma serotonergic pathway were altered both by the type of feed consumed and the duration of feeding. The urine serotonergic pathway was affected by mainly the duration for which a particular diet was consumed. These findings may have implications in the feeding behavior, cognitive decline and depression associated with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Most peripheral 5-HT is produced by enterochromaffin cells (Ecs) in the intestine and stored in platelets (Figure 1; Jones et al, 2020). Studies have demonstrated that fasting and feeding high-carbohydrate or high-fat foods to mice increases plasma 5-HT levels (Stephen and Abraham, 2019). Peripheral 5-HT acts as a signaling molecule in the gastrointestinal tract to activate the corresponding receptors and participate in a variety of human physiological activities.…”
Section: Tryptophan Metabolic Pathwaymentioning
confidence: 99%
“…Most peripheral 5-HT is produced by enterochromaffin cells (Ecs) in the intestine and stored in platelets (Figure 1; Jones et al, 2020). Studies have demonstrated that fasting and feeding high-carbohydrate or high-fat foods to mice increases plasma 5-HT levels (Stephen and Abraham, 2019). Peripheral 5-HT acts as a signaling molecule in the gastrointestinal tract to activate the corresponding receptors and participate in a variety of human physiological activities.…”
Section: Tryptophan Metabolic Pathwaymentioning
confidence: 99%